Key success factors of SME Internationalisation : a cross-country perspective - Dominguez, Noémie; Mayrhofer, Ulrike (International business and management series ;, 2018)
This collectivebook offers a cross-country perspective on the internationalisation of smalland medium-sized enterprises (SMEs). Scholars from prestigious institutions in Europe,North America, Australia and China provide new insights on how SMEs develop andperform their international activities. Their innovative approach isparticularly useful to understand the major role played by SMEs in todaysglobal economy. The authorsidentify key factors that facilitate the international expansion of SMEs. Theyexplain how SMEs can succeed in their development in both mature and emergingeconomies. Their findings are based on quantitative surveys and in-depthcase studies, and the resulting recommendations are provided to help SME managers increase theperformance of their international activities.